Point-of-Care Testing at the Disaster-Emergency-Critical Care Interface - Tran, Nam K. (2012)
Point-of-care (POC) testing allows for medical testing to be performed across the disaster-emergency-critical care continuum. The disaster-emergency-critical care continuum begins with the identification of at-risk patients, followed by patient stabilization, and ultimately transfer to an alternate care facility or mobile hospital for comprehensive critical care. Gaps at the interfaces for each of these settings leads to excess mortality and morbidity. Disaster victims are at risk for acute myocardial infarctions, acute kidney injury (AKI), and sepsis. However cardiac biomarker testing, renal function testing, and multiplex rapid pathogen detection are often unavailable or inadequate during disasters. Cardiac biomarker reagents require refrigeration; traditional renal function tests (i.e., serum creatinine) exhibit poor sensitivity for predicting AKI in critically ill patients, and culture-based pathogen detection is too slow to help initiate early-directed antimicrobial therapy. We propose three value propositions detailing how rapid, POC, and environmentally hardened cardiac biomarker, AKI and multiplex pathogen testing harmonizes the interface between disaster, emergency, and critical care.